Sedimentary mercury enrichments as a tracer of large igneous province volcanism - Percival, LME; Berguist, BA; Mather, TA; Sanei, H (American Geophysical Union, 2021)
Volcanic activity associated with the emplacement of Large Igneous Provinces (LIPs) has been linked to most Phanerozoic extinctions/episodes of major environmental change. In recent years, mercury (Hg) enrichments and elevated mercury/total organic carbon (Hg/TOC) ratios have been increasingly utilized as a marker of volcanism in sedimentary records deposited distally from LIPs. The proxy is based on the premise that volcanism is a major natural source of the element to the atmosphere, and was especially important prior to anthropogenic emissions. To date, end-Permian and end-Triassic records illustrate the strongest use of Hg as a volcanic proxy; aided by supporting evidence (including Hg isotopes) for LIP eruptions and/or volatile emissions. Sedimentary records of several other events also document Hg enrichments in at least one region, suggesting regional or global Hg-cycle perturbations potentially linked to volcanism at those times. The Cenomanian-Turonian Oceanic Anoxic Event appears to be an exception, with Hg/TOC peaks documented in a small minority of studied records, suggesting minimal Hg-cycle disturbance at that time. Even for events that apparently featured a global-scale Hg-cycle perturbation, variable Hg enrichments across individual archives of that same crisis indicate that the complex biogeochemical cycling of the element can strongly influence local/regional aquatic, biological, or sedimentary processes to alter the precise signature of any worldwide disturbance. Recent studies are beginning to investigate these complexities, but further work is needed to fully explore the nuances of Hg in the geological record, and how it can be best employed as a proxy for LIP volcanism.